Hambatan, kebutuhan dan ambivalensi reaksi terhadap kebijakan publikasi internasional di Indonesia - Rindi Ardika Melsalasa Sahputri; Bambang Santoso Haryono; Sujarwoto Sujarwoto (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
In the efforts of internasionalization, change has been occurred in academia organisations in Indonesia. In higher education, there are several changes in research fields which was driven to publish international publications. While implementing this change, there was often an ambivalent reaction, both supporting change and opposing change. This ambivalent reaction will inhibit change and prompt counterproductive employees. Therefore, it is important to identify these reactions and factors associated with these reactions among organizational members. This study aims to investigate lecturers’ ambivalence regarding their responses to international publication policy.. This study also investigates the effect of employees’ personalitieson ambivalence reaction and the moderating effect.This study used a crossectional approach. Data were collected through lecturers in 5 social science faculties in a public university in Indonesia, using online questionnaire via google form. The instrument of ambivalence reaction are based on attitude toward change scale.Regression analysis was used to estimates the correlation, and interaction analysis was calculated to test the moderating effect. This study found that dispositional resistance to change’ personalitysignificantly correlated with ambivalence reaction.And the correlation was moderated by employee’s high trust in organization.However this study did not found a significance difference on low trust in management, dispositional resistance to change, and ambivalence. This study also found the challenges and the lecturer’s needs to publish in international publications.